ANALYSIS UNDERSTANDING OF CONCEPT IN SOUND WAVE MATERIALS AND LIGHT WAVES IN CLASS XI SENIOR HIGH SCHOOL STUDENTS TAMPAN PEKANBARU - Nindri Resti Nova; Fakhruddin Z; Yennita Yennita (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
The main purpose of this research was to know the level of understanding of students’ concepts in the sound wave and light waves material in class XI students of senior high school in the sub-district of Tampan, Pekanbaru. This research is survey research. The population in this research were all students of class XI of state Senior high schools in the Tampan sub-district of Pekanbaru, while the research sample numbered 65 students. The research instrument was in the form of concept understanding tests that were compiled based on indicators understanding the concepts of translation, interpretation, and extrapolation. The questions used were in the form of a written test in the form of multiple-choice totaling 26 items. The results of the answers to the questions given are then analyzed using descriptive analysis. The results of this research provide information, that the level of concepts understanding of class XI students in high schools throughout the sub-district of Tampan, Pekanbaru in physics lessons on sound wave material and light waves are in the very low category for the three indicators of translation, interpretation, and extrapolation. Therefore, a learning strategy is needed that is able to overcome the low understanding of the student's concepts.